Time Management of FPOK UPI Students in Balancing Academic and Non-Academic Activities with the Implementation of Fardhu Prayers: A Phenomenological Study: Studi Fenomenologi - Aulia Cahya Nur; Tya Fauzyyah Suciyanti; Nabila Alwini Saleh; Fakhira Nishfillailya Ramadhany; Muhamad Parhan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to describe the experiences of students at the Faculty of Sports and Health Education (FPOK) of the Indonesia University of Education in managing their time amid busy academic activities, sports practicums, non-academic activities, and the performance of fardhu prayers. The study used a phenomenological approach with in-depth interviews with three students, one FPOK lecturer, and one MKDU lecturer. Analysis was conducted through data reduction and interpretation of the meaning of experiences. The results showed that students faced challenges such as physical fatigue, overlapping practice schedules, academic pressure, and prayer times that often conflicted with afternoon training sessions. Nevertheless, students still showed strong commitment to performing prayers. The FPOK lecturer emphasized the need for a written policy regarding the adjustment of practice schedules with prayer times, while the MKDU lecturer emphasized the importance of a transition space so that students could recover physically before performing prayers. This study confirms that the balance between physical, academic, and spiritual activities is an important component in sports education.